Observation of plasma-facing-wall via high dynamic range imaging - Villamayor, Michelle Marie S. (Animo Repository, 2013)
Pictures of plasmas and deposits in a discharge chamber taken by varying shutter speeds have been integrated into high dynamic range (HDR) images. The HDR images of a graphite target surface of a compact planar magnetron (CPM) discharge device have clearly indicated the erosion pattern of the target, which are correlated to the light intensity distribution of plasma during operation. Based upon the HDR image technique coupled to colorimetry, a formation history of dust-like deposits inside of the CPM chamber has been recorded. The obtained HDR images have shown how the patterns of deposits changed in accordance with discharge duration. Results show that deposition takes place near the evacuation ports during the early stage of the plasma discharge. Discoloration of the plasma-facing-walls indicating erosion and redeposition eventually spreads at the periphery after several hours of operation.